Developing renewable energy in developing countries: A lesson from Indonesia - Nugroho, H. (Taylor and Francis Inc., 2017)
Global energy consumption grows faster than world population. It is projected that the next growth will be driven by developing countries in Asia region. As energy consumption rises, the awareness of environmental issues related with fuel and energy consumption gradually grows. One solution for these issues is the use of renewable energy. However, it has its own challenges. Besides its high up-front cost, the technological barriers of renewable energy are different from one country to another. Therefore, in this study, we took the learning curve in Indonesia as a lesson. The energy supply in Indonesia is dominated by nonrenewable energy resources. The government however is committed to renewal energy, and its growth is promising. We conclude that two markets are potential in developing countries. First is the implementation of renewable energy in rural area. This implementation should take into account rural entrepreneurship. Second is the implementation of renewable energy for grid-connected power production. Policy must overcome political and institutional obstacles and consider utility-sector issues. © 2017 Taylor & Francis Group, LLC.